New method for observing self-heating effect using transistor efficiency signature - Mori, C. A. B. (2017)
This paper reports a new method for observing the presence of self-heating effect through transistor efficiency (gm/ID) signature from DC measurements, for fast and accurate analysis. This new method is tested first through numerical simulations employing simple analytical models, and then applied experimentally. The transistor efficiencies of short and long channel pFinFETs were used for experimental observation of self-heating effects in this paper. It is possible to see if the self-heating is weak, moderate or strong through the signature format observed on gm/ID versus ID curve.